Geomatics for studying historic supply systems: the Grotta degli Animali case study. Issue 1 (November 2020) - Tucci, G; Bonora, V; Conti, A; Fiorini, L
Abstract: In the past, it was difficult to exhaustively document gardens and artificial grottoes with traditional manual survey techniques and maybe also for this reason the restoration Charters used to pass over the need of an accurate survey. Currently, high resolution sampling allows to obtain 3-D data acquisition and realistic and metrically accurate representations. However, the quality of a digital model is not validated by automatic measures or likelihood but following rigorous acquisition and processing workflows, which must be described in metadata and paradata. The new survey reveals some aspects of the historic water supply system for a better understanding of the construction of this monument and will be extended to the narrow tunnels included in the retaining wall around the grotto.